2019
DOI: 10.1016/j.talanta.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a smartphone-based biomimetic sensor for aflatoxin B1 detection using molecularly imprinted polymer membranes

Abstract: A novel smartphone-based optical biomimetic sensor based on free-standing molecularly imprinted polymer (MIP) membranes was developed for rapid and sensitive point-of-care detection of aflatoxin B1. The developed MIP membranes were capable of selective recognition of the target analyte and, at the same time, of generation of a fluorimetric sensor response, which could be registered using the camera of a smartphone and analysed using image analysis. The developed system provides a possibility of synchronous det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 23 publications
1
66
0
Order By: Relevance
“…Biosensors combining novel materials have been well received because this method avoids tedious instrument operation. Sergeyeva et al (2019) reported an MIP biosensor based on a smartphone for AFB1 detection. MIP membranes with binding sites were constructed by in situ polymerization with acrylamide (AA) and 2-(diethylamino)ethylmethacrylate (AMPSA) as functional monomers.…”
Section: Fluorescence Biosensors Based On Mipsmentioning
confidence: 99%
“…Biosensors combining novel materials have been well received because this method avoids tedious instrument operation. Sergeyeva et al (2019) reported an MIP biosensor based on a smartphone for AFB1 detection. MIP membranes with binding sites were constructed by in situ polymerization with acrylamide (AA) and 2-(diethylamino)ethylmethacrylate (AMPSA) as functional monomers.…”
Section: Fluorescence Biosensors Based On Mipsmentioning
confidence: 99%
“…The LoD was 3.9 pg/mL with 3δ/slope calculation. Compared with the smartphone-based fluorimetric sensor system for AFB1 detection proposed in reference [20], which has a linear range of 20-100 ng/mL (R 2 = 0.98), and a detection limit of 20 ng/mL, our FICA strip reader has a wider application range due to its lower LoD.…”
Section: Curve Fittingmentioning
confidence: 99%
“…Four milliliters (10 μg/mL) AFB1 solution (prepared in methanol-water) was added into the tubes. The mixture was vigorously shaken at 2500 rpm for a series of time (1,2,3,6,9,12,15,20,25,30,35,40, and 60 min). The tubes were centrifuged and the supernatants were measured by HPLC.…”
Section: Dynamics Of Polymersmentioning
confidence: 99%